Retrofitting and rehabilitation of vernacular housing in flood prone areas in Sri Lanka. (September 2021) - Platt, Shawn L.; Ranasinghe, Gihan; Jayathilaka, H.A.D.G.S.; Jayasinghe, C.; Jayasinghe, M.T.R.; Walker, Pete; Maskell, Daniel
Abstract: This paper presents findings from an investigation into applications to improve the structural resilience and safety of low-rise vernacular masonry homes when subject to extreme flooding. In 2016 and 2017 flooding brought devastation throughout many areas in Sri Lanka. Findings from field investigations to evaluate, characterize, and quantify the extent and nature of structural damage to low rise vernacular masonry houses from these flood events are presented. Low cost solutions were developed to enhance the flexural capacity of masonry walls using reinforced plasters. Single storey homes in rural areas are particularly at risk from rapid flood events, and limited evacuation opportunities require a means of in-situ refuge. Focusing on these risks, a unique retrofitting project, including an elevated refuge area for occupants to escape and shelter during flood events, is also presented. This research will directly improve the welfare of vulnerable communities living in flood risk areas, minimizing the risk of flood induced structural failure, while enabling people to safely remain in their homes. Highlights: Improve the structural flood resilience of low-rise vernacular masonry homes. Field surveys are used to evaluate the extent and nature of structural flood damage. Novel retrofitting solutions enhance the flexural capacity of saturated masonry walls. Elevated refuge area for occupants to shelter during flood events is presented. Objective of mitigating flood impacts and keeping families in their original homes.